La influencia de juegos en el desarrollo de las destrezas y habilidades de las niñas y niños de primer año de educación básica en la escuela María Montessori de la parroquia Tenguel, cantón Guayaquil, provincia del Guayas en el periodo lectivo 2012 - 2013. - Carraza Beltrán, Glenda Maribel (2013)
To conduct the research, I proposed the following objectives for agreements to variable presented. To determine the importance of playgrounds for the development of the skills and abilities of students in first year of basic school education Montessori the Tenguel parish in the 2012 academic year - 2013, 2.-Analyze the influence of the playground in the process of learning of students in their first year of primary school education Montessori the Tenguel parish in the academic year 2012 - 2013, 3. To determine the relationship between the playgrounds and meaningful learning of freshmen basic school education Montessori the Tenguel parish in the 2012 academic year - 2013, that allowed the specific objectives comply with the investigation. The investigation pursuant to nature and is essentially descriptive characteristics and features in the literature assumes as theoretical framework is based on recognized and prestigious authors. Furthermore, it is documentary that analyzes the characteristics, historical development and current situation of selected educational establishment. But research will mainly field as interview guides and observation guide the social actors involved in the problem under study are involved, we rely on the inductive method, deductive method, and hypothetical - deductive, as technical We apply the technique of interviews and literature. As shown we, 2 teachers and 70 parents of families in the first year of basic education of the Fiscal School Maria Montessori with the investigation, it is provided with a proposal to mobilize the classroom to reinforce the knowledge of teachers and to enhance the inclusion of the game in the first year students of basic education also that the conclusions they arrive, they constitute the starting point for future research on the subject.